Mind over mood: exploring the executive function’s role in downregulation - Rodas, Jose A.; Leon-Rojas, Jose; Rooney, Brendan (Frontiers in Psychology, 2024)
Emotion regulation plays a key role in well adapted behaviour, however, factors influencing individual differences in ER are still under investigation. Across two studies we investigate the complex relationship between executive functions (EFs) and emotional downregulation through two complementary research designs. The focus lies on key components of EFs—working memory, inhibitory control, and switching—and their relationship with effective emotional regulation. Surprisingly, switching emerged as the sole significant predictor in two multiple linear regression models, challenging the conventional belief that all major EFs broadly contribute to emotional downregulation. The first study, involving 248 Ecuadorian adults between 18 and 60 years old, used experimental tasks to assess the association between EFs and emotional regulation, aligning with existing literature that posits a link between EFs and emotional control. The second study, involving 180 Ecuadorian adults between 18 and 43 years old, added depth by incorporating self-report measures, providing a broader, ecologically valid perspective. However, these measures did not significantly predict downregulation, highlighting a gap between self-perception and actual cognitive abilities. Additionally, demographic predictors varied between the two studies, urging future research to consider methodological design and task selection carefully. The study also raises questions about the validity of commonly used measures, emphasising the need for more nuanced tools to capture the complexity of EFs and emotional regulation. Our findings suggest a targeted research avenue focusing on EFs for both future research and clinical interventions. Attention is called to the methodological decisions that can influence the observed associations, and the need for broader demographic representation in future studies.